2022
DOI: 10.1021/acs.jafc.2c03411
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Methylglyoxal Exposure Induces Alzheimer’s Disease by Promoting Amyloid β Accumulation and Disrupting Autophagy in Caenorhabditis elegans

Abstract: Methylglyoxal (MG) is a precursor of advanced glycation end products usually generated during cooking. The high level of MG in the brain is correlated to the pathogenesis of Alzheimer’s disease (AD). However, it is not clear if MG consumed through the diet can cause AD-related toxicity. Herein, the Caenorhabditis elegans (C. elegans) AD model was used to investigate the neurotoxicity after long-term MG exposure at dietary levels. The results showed that C. elegans locomotive behaviors were significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These experiments suggested that the methylglyoxal, a precursor compound of AGEs, activates the membrane-bound NADPH oxidase (NOX), thereby leading to the expression of inflammatory markers, and the accompanying astroglial and microglial activation and synaptic dysfunction in animal models as well as in AD patients. Dietary methylglyoxal was also shown to induce AD through the increased expression of amyloid-β (Aβ) in AD models of Caenorhabiditis elegans ( C. elegans ) [ 87 ]. It was demonstrated that the use of a citrus flavonoid, nobiletin, attenuated the methylglyoxal-induced toxicity [ 87 ].…”
Section: Rage and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments suggested that the methylglyoxal, a precursor compound of AGEs, activates the membrane-bound NADPH oxidase (NOX), thereby leading to the expression of inflammatory markers, and the accompanying astroglial and microglial activation and synaptic dysfunction in animal models as well as in AD patients. Dietary methylglyoxal was also shown to induce AD through the increased expression of amyloid-β (Aβ) in AD models of Caenorhabiditis elegans ( C. elegans ) [ 87 ]. It was demonstrated that the use of a citrus flavonoid, nobiletin, attenuated the methylglyoxal-induced toxicity [ 87 ].…”
Section: Rage and Gut Microbiotamentioning
confidence: 99%
“…Dietary methylglyoxal was also shown to induce AD through the increased expression of amyloid-β (Aβ) in AD models of Caenorhabiditis elegans ( C. elegans ) [ 87 ]. It was demonstrated that the use of a citrus flavonoid, nobiletin, attenuated the methylglyoxal-induced toxicity [ 87 ]. Other polyphenolic compounds, including ss-caryophyllene and carnosic acid, and camellia oil were also demonstrated to show anti-inflammatory activity and thus act as potential neuroprotective compounds [ 85 , 88 , 89 ].…”
Section: Rage and Gut Microbiotamentioning
confidence: 99%
“…The same cohort had less low‐grade inflammation in participants with a higher habitual intake of MGO (Maasen, Eussen, Dagnelie, et al., 2022 ). Prolonged exposure to high levels of MGO in animals induced various negative effects like decreased locomotive behavior and promoted amyloid β accumulation in Caenorhabditis elegans (Wei et al., 2022 ) and oxidative stress and endothelial dysfunction in rats (Sena et al., 2012 ). On the other hand, long‐term oral application of MGO had no adverse effects on physical performance and organs in rabbits, rats, mice, and dogs (Ghosh et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%